Implementation and Management of Fcse Laboratories Environment - Bidikov, Vladislav; Kjiroski, Kiril; Jakimovski, Boro (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
The Computer Center at Faculty of Computer Sciences and Engineering worNs on continual improving the networN environment at the campus, through implementation of modern technologies. These technologies enable better worN environment for students as well as faculty staff. Due to the fact that the faculty has a substantial number of laboratories with worNstations and personal computers, improvement of the networN security and networN performance represents a Ney factor in the worNing process. In order to achieve these goals, the FCC team combines software solutions which provide efficient networN management, and fast and optimized deployment of software on the computers at campus laboratories. Due to the past experience, as well as experimentation with current Open-source software solutions, we decided to implement ClearOS as a tool for networN management, and we chose FOG as a PXE image solution for the deployment of software. Used software provides scalable and user friendly solutions which enable fast and easy deployment. The initial implementation resulted in increased networN manageability as well as rapid deployment of campus computers. As a result, the FCSE Computer Center can promptly respond to the dynamic changes in needed and used software for teaching and learning processes at the faculty.